2000
DOI: 10.3109/08820130009062292
|View full text |Cite
|
Sign up to set email alerts
|

The Role of CD40-CD154 Interactions in the Regulation of Cell Mediated Immunity

Abstract: CD40 is expressed on a diverse array of cell types from the hematopoietic and non-hematopoietic compartments. Within the hematopoietic compartment, CD40 is found constitutively expressed on B cells, dendritic cells (DC) and macrophages. The function of CD40 in B cells has been documented as being essential in the control of humoral immunity. In DCs and macrophages, CD40 has been shown to be important in the induction of antigen-presenting cell (APC) maturation and effector function. CD40 is also expressed on n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
33
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 9 publications
0
33
0
2
Order By: Relevance
“…CD154 (CD40 ligand [CD40L]), a member of the tumor necrosis factor (TNF) ligand family, is expressed primarily on the surfaces of activated T cells and plays several key roles in the regulation of cellular immune responses (46). Studies have demonstrated that intracellular communications via the CD40-CD154 pathway can upregulate costimulatory molecules, activate antigen-presenting cells (APCs), and influence T-cell-mediated effector functions (15,27). The CD40-binding regions of CD154 have been identified (41), and this information was recently used in our laboratories to engineer a bacterium that displays these CD40-binding regions on its surface, resulting in an enhanced immune response against a copresented foreign peptide sequence (10,24).…”
mentioning
confidence: 99%
“…CD154 (CD40 ligand [CD40L]), a member of the tumor necrosis factor (TNF) ligand family, is expressed primarily on the surfaces of activated T cells and plays several key roles in the regulation of cellular immune responses (46). Studies have demonstrated that intracellular communications via the CD40-CD154 pathway can upregulate costimulatory molecules, activate antigen-presenting cells (APCs), and influence T-cell-mediated effector functions (15,27). The CD40-binding regions of CD154 have been identified (41), and this information was recently used in our laboratories to engineer a bacterium that displays these CD40-binding regions on its surface, resulting in an enhanced immune response against a copresented foreign peptide sequence (10,24).…”
mentioning
confidence: 99%
“…26 A soluble form of CD40L can bind CD40 receptor expressed on a variety of cells, such as endothelial cells, platelets, macrophages, B cells and vascular smooth muscle cells, resulting in inflammatory responses. 27 The goal of the present study was to evaluate the effects of ATG on coagulation and endothelial cell activation in patients undergoing allo-SCT by testing coagulation and thrombophilia markers, as well as circulating total and endothelial microparticles (TMP/EMP) and soluble CD40L.…”
Section: Discussionmentioning
confidence: 99%
“…This interaction is known to deliver a bidirectional second signal, which is able to simultaneously activate both the effector T cells and the APC, increasing their priming ability (17). Many researchers believe that the interaction between CD40 and CD40L is critical for helping the APC to efficiently prime CD8 ϩ -specific cytotoxic cells (17).…”
mentioning
confidence: 99%
“…ϩ Th cells (17). This interaction is known to deliver a bidirectional second signal, which is able to simultaneously activate both the effector T cells and the APC, increasing their priming ability (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation